HIV Seroconversion in the Era of Pharmacologic Prevention: A Case–Control Study at a San Francisco STD Clinic. (1st October 2019) - Johnson, Kelly A.; Hessol, Nancy A.; Kohn, Robert; Nguyen, Trang Q.; Mara, Elise S.; Hsu, Ling; Scheer, Susan; Cohen, Stephanie E.
Abstract : Background: The comparative effectiveness of pre- and post-exposure prophylaxis (PrEP and PEP) for men who have sex with men (MSM) is unclear. Setting: We conducted a case–control study of MSM who were initially HIV-uninfected during September 1, 2012–June 30, 2016 at San Francisco's only municipal sexually transmitted diseases (STDs) clinic. Methods: Each case was matched with up to 3 controls based on age, baseline visit date, and follow-up time. The primary dependent variable was HIV seroconversion; the primary independent variable was exposure to PrEP, PEP, or neither. Conditional logistic regression was used to calculate odds ratios and 95% confidence intervals. Results: Of 638 MSM (161 cases and 477 controls), 137 reported ever taking PrEP, 98 reported taking PEP-only, and 403 took neither. PrEP takers had more non-HIV sexually transmitted diseases during the analysis (72.3% vs. 55.1% vs. 42.4% P < 0.01) and were more likely to report receptive anal sex in the past 3 months (86.5% vs. 80.4% vs. 73.0%; P < 0.01). In the adjusted model, PrEP was associated with lower odds of HIV seroconversion (odds ratio 0.24; 95% confidence interval: 0.13 to 0.46) while PEP use had no effect on HIV acquisition compared with taking neither. Conclusions: MSM who ever used PrEP demonstrated equal or higher sexual risk compared with those using neither PrEP nor PEP but had 76% lower odds of HIV seroconversion. MSM who used PEP but never PrEP were no less likely to seroconvert than those using neither. MSM should be offered PrEP. PEP users with ongoing risk of HIV infection should be connected to PrEP after PEP. Abstract : Supplemental Digital Content is Available in the Text.